THE INFORMATION QUALITY EFFECT: ENHANCING USER ENGAGEMENT AND PURCHASE INTENT IN E-COMMERCE - Santos, Marcelo Henrique; Ferreira, Ana Carolina (Ayden Journal of Management and Social Sciences, 2024)
The way customers make purchasing decisions has evolved in the digital age, with consumers utilizing both online and offline channels to research products, compare prices, and find the best deals. This shift in consumer behavior necessitates research that helps businesses effectively integrate various communication channels to provide superior service and enhance overall company performance. Understanding the determinants of customer purchase intention is essential in this context. Ecommerce, driven by the internet's rapid expansion, has garnered considerable attention from both researchers and marketing professionals. The changing landscape of customer behavior in the multimedia environment, characterized by multiple screens and communication channels, presents new research opportunities. This study aims to explore the impact of social media and digital technology on customer experiences and the decision-making process. By examining these emerging consumer behaviors, businesses can adapt their strategies to meet evolving customer preferences.